Penumbuhan Lapisan Tipis µc-Si:H dengan Sistem Hot Wire PECVD untuk Aplikasi Divais Sel Surya - Syamsu Syamsu; Darsikin Darsikin; Iqbal Iqbal; Jusman Jusman; Toto Winata; Sukirno Sukirno; Mohamad Barmawi (Institut Teknologi Bandung, 2005)
Microcrystalline hydrogenated silicon thin films have been grown on corning 7059 by using Hot Wire Plasma Enhanced Chemical Vapor Deposition (PECVD) system. Silane gas dilute in hydrogen gas (SiH4: H2 = 1 : 10 ) used as gas source. The effect substrate temperatures on deposition rate, optical, electrical and structural properties were analyzed. The deposition rate was varied from 3.22-5.24 µm/hour at temperature 175-275o C, SiH4 flow rate of 70 sccm, and filament temperature 1000oC. The optical band gap varied from 1.13-1.44 eV at substrate temperature of 175-275. The Result XRD characterization of µc-Si: H thin film was grown at 275o C shows , , and orientation. Dark conductivities vary from 10-6-10-4 S/cm The Dark conductivity of µc-Si: H is higher than a-Si: H thin film. This result shows that µc-Si: H thin film is possible for p-i-n solar cells device application.